Exploring TOEFL Anxiety in First-Time Test-Takers: Emotional, Cognitive, and Motivational Perspectives - Asma Asma; Khairul Azmy; Nur Akmaliyah; Sri Kartika Abdul Rahman (Universitas Islam Negeri (UIN) Sultanah Nahrasiyah Lhokseumawe, 2026)
The present study examined the test anxiety of TOEFL among non-English major college students who took the test for the first time. The aim is to explore emotional responses, cognitive problems, and motivational-behavioural implications associated with TOEFL anxiety. A descriptive qualitative study was adopted and six first-time TOEFL test takers were selected using purposive sampling. Data were collected through semi-structured interviews and analysed using descriptive thematic analysis to identify common themes across participants’ experiences. The results of the study suggest that students showed less anticipatory fear at the start but experienced more emotional pain during the test, especially during the Listening segment. The anxiety experienced was in the form of fear of failing, difficulty concentrating and lack of self-confidence, in accordance with theories of language anxiety that underline the effect of assessment pressure and perceived language proficiency. Cognitive obstacles included a limited vocabulary, problems with auditory information processing and poor strategy use which led to cognitive overload and reduced efficiency in performance. There were cognitive distortions among participants such as an overestimation of the task difficulty and underestimation of their talents, contributing to increased anxiety during test performance. TOEFL anxiety had also positive motivating effects, students reported an increased motivation to learn, improved study habits, and greater engagement in practicing English. Methods of coping included self-encouragement, support from friends and parents and constant practice, which eased anxiety and increased resilience. The statistics imply that TOEFL anxiety is a multidimensional entity consisting of emotional, cognitive and behavioural components which interact dynamically during test performance. The results highlight the significance of structured TOEFL preparation programs that integrate language skill building with anxiety reduction approaches to improve student readiness and performance on crucial English proficiency tests.